2021
DOI: 10.5114/biolsport.2021.104920
|View full text |Cite
|
Sign up to set email alerts
|

Professional football in times of COVID-19: did the home advantage effect disappear in European domestic leagues?

Abstract: This study aimed to examine how the home advantage (HA) and home teams’ performances changed in European football leagues (German Bundesliga, Spanish La Liga, English Premier League, Portuguese Primeira Liga and Italian Serie A) with the measures imposed by legal authorities to deal with the COVID-19 pandemic (no audience, five substitutions and “cooling breaks”). The HA (Pollard’s rescaled method) and home performance-related statistics of matches contested before (n = 491) and after (n = 491) the 2019–2020 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…This observation was further confirmed in a systematic literature review by Leitner et al (2022) , who identified 26 studies that analyzed the last portion of the 2019–20 season, when all matches were played behind closed doors. Out of these 26 studies, only six did not observe a significant and consistent overall decrease of the home advantage and referee bias in the considered leagues ( Almeida & Werlayne, 2021 ; Benz & Lopez, 2021 ; Krawczyk & Strawinski, 2020 ; Matos et al, 2021 ; Ramchandani & Millar, 2021 ; Wunderlich et al, 2021 ), while the other 20 ones did observe a significant decrease of these phenomena ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Cross & Uhrig, 2020 ; Cueva, 2020 ; Dilger & Vischer, 2020 ; Endrich & Gesche, 2020 ; Ferraresi & Gucciardi, 2020 , 2021 ; Fischer & Haucap, 2020 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Konaka, 2021 ; Leitner & Richlan, 2021a ; Link & Anzer, 2021 ; McCarrick et al, 2021 ; Rovetta & Abate, 2021 ; Santana, Bettega & Dellagrana, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ; Tilp & Thaller, 2020 ). Considering exclusively the peer-reviewed, multi-leagues studies, they found that nine out of 13 studies observed such a decrease ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Ferraresi & Gucciardi, 2021 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Leitner & Richlan, 2021a ; McCarrick et al, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ).…”
Section: Introductionmentioning
confidence: 94%
“…This observation was further confirmed in a systematic literature review by Leitner et al (2022) , who identified 26 studies that analyzed the last portion of the 2019–20 season, when all matches were played behind closed doors. Out of these 26 studies, only six did not observe a significant and consistent overall decrease of the home advantage and referee bias in the considered leagues ( Almeida & Werlayne, 2021 ; Benz & Lopez, 2021 ; Krawczyk & Strawinski, 2020 ; Matos et al, 2021 ; Ramchandani & Millar, 2021 ; Wunderlich et al, 2021 ), while the other 20 ones did observe a significant decrease of these phenomena ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Cross & Uhrig, 2020 ; Cueva, 2020 ; Dilger & Vischer, 2020 ; Endrich & Gesche, 2020 ; Ferraresi & Gucciardi, 2020 , 2021 ; Fischer & Haucap, 2020 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Konaka, 2021 ; Leitner & Richlan, 2021a ; Link & Anzer, 2021 ; McCarrick et al, 2021 ; Rovetta & Abate, 2021 ; Santana, Bettega & Dellagrana, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ; Tilp & Thaller, 2020 ). Considering exclusively the peer-reviewed, multi-leagues studies, they found that nine out of 13 studies observed such a decrease ( Bryson et al, 2021 ; Correia-Oliveira & Andrade-Souza, 2021 ; Ferraresi & Gucciardi, 2021 ; Hill & Van Yperen, 2021 ; Jimenez Sanchez & Lavin, 2021 ; Leitner & Richlan, 2021a ; McCarrick et al, 2021 ; Scoppa, 2021 ; Sors et al, 2021 ).…”
Section: Introductionmentioning
confidence: 94%
“…In turn, for individual teams, HA can be measured by comparing a single team’s home performance with its away performance (i.e., the percentage a single team’s home wins in relation to all wins, both at home and away) (Pollard & Gomez, 2007b). This measure is always non-negative and varies from 0% (no games won at home) to 100% (no games won away), with a value of 50% representing an equal number of points won at home and away (i.e., no home advantage) ( Almeida & Leite, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Matos et al (2021) examined HA in the Portuguese major soccer league and did not find changes due to the absence of the crowd, either in the comparison with games from the 2019/2020 season or in the comparison with previous seasons. Almeida and Leite (2021) also reported divergent results for several European leagues due to the absence of crowds in the stadiums. While HA was reduced in some leagues, the absence of the crowd support did not seem to affect HA in others.…”
Section: Introductionmentioning
confidence: 99%